2012
DOI: 10.1063/1.4768261
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and optical properties of vacancy-doped WS2 monolayers

Abstract: Monolayers of tungsten disulfide doped with atomic vacancies have been investigated for the first time by density functional theory calculations. The results reveal that the atomic vacancy defects affect the electronic and optical properties of the tungsten disulfide monolayers. The strongly ionic character of the W-S bonds and the non-bonding electrons of the vacancy defects result in spin polarization near the defects. Moreover, the spin polarization of single W atomic vacancies has a larger range than for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…Recent experimental as well as theoretical studies have demonstrated that sulfur vacancies are the dominant source of disorder in MoS 2 [13][14][15][16][17][18]. In the following we will therefore focus exclusively on sulfur vacancies, and calculate their effect on the VHC.…”
Section: Disordered Mosmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experimental as well as theoretical studies have demonstrated that sulfur vacancies are the dominant source of disorder in MoS 2 [13][14][15][16][17][18]. In the following we will therefore focus exclusively on sulfur vacancies, and calculate their effect on the VHC.…”
Section: Disordered Mosmentioning
confidence: 99%
“…It is well established that sulfur vacancies constitute the main source of disorder in MoS 2 [13][14][15][16][17][18]. The formation energies and thermodynamics of these defects have been thoroughly studied [19], but their influence on transport and optical properties remains largely unexplored.…”
Section: Monolayers Of Mosmentioning
confidence: 99%
“…Similar exfoliation in aqueous solution instead of organic solvents has also been reported [15]. However, defect-free WS2 has been difficult to obtain, and imperfections including sulfur vacancy defects and oxidized impurities may strongly affect the transport properties of the materials [16,17]. In our previous work, we have developed a facile low-temperature thiol chemistry route to repair the sulfur vacancies and improve the electrical properties [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, adatom adsorption and doping on ML MX 2 is especially achievable by virtue of their 2D surface nature. Both the naturally occurring and chemically or physically introduced point defects in MX 2 will extensively modulate the physical properties such as charge transport, magnetism, optical absorption, and absorbability [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], thus control the applicability of the material. The crucial role of point defects has triggered many studies to investigate their behavior in ML MX 2 .…”
Section: Introductionmentioning
confidence: 99%